Pulmonary Metastasectomy in Colorectal Cancer: updated analysis of 93 randomized patients – control survival is much better than previously assumed. (14th June 2020) - Milosevic, M.; Edwards, J.; Tsang, D.; Dunning, J.; Shackcloth, M.; Batchelor, T.; Coonar, A.; Hasan, J.; Davidson, B.; Marchbank, A.; Grumett, S.; Williams, N.R.; et al.
Abstract: Aim: Lung metastases from colorectal cancer are resected in selected patients in the belief that this confers a significant survival advantage. It is generally assumed that the 5‐year survival of these patients would be near zero without metastasectomy. We tested the clinical effectiveness of this practice in Pulmonary Metastasectomy in Colorectal Cancer (PulMiCC), a randomized, controlled noninferiority trial. Method: Multidisciplinary teams in 14 hospitals recruited patients with resectable lung metastases into a two‐arm trial. Randomization was remote and stratified according to site, with minimization for age, sex, primary cancer stage, interval since primary resection, prior liver involvement, number of metastases and carcinoembryonic antigen level. The trial management group was blind to patient allocation until after intention‐to‐treat analysis. Results: From 2010 to 2016, 93 participants were randomized. These patients were 35–86 years of age and had between one and six lung metastases at a median of 2.7 years after colorectal cancer resection; 29% had prior liver metastasectomy. The patient groups were well matched and the characteristics of these groups were similar to those of observational studies. The median survival after metastasectomy was 3.5 (95% CI: 3.1–6.6) years compared with 3.8 (95% CI: 3.1–4.6) years for controls. The estimated unadjusted hazard ratio for death within 5 years, comparing the metastasectomy group with the control group, was 0.93 (95% CI: 0.56–1.56). Use of chemotherapy or local ablation was infrequent and similar in each group. Conclusion: Patients in the control group (who did not undergo lung metastasectomy) have better survival than is assumed. Survival in the metastasectomy group is comparable with the many single‐arm follow‐up studies. The groups were well matched with features similar to those reported in case series.